Chest Deformity and Disability due to Tenofovir-Induced Hypophosphatemic Osteomalacia: Case Report and Call for Improved Global Access to Laboratory Testing. (September 2017) - Hajek, Jan; Ouma, Simple; Hemmett, Juliya; Starko, Rob; Apiyo, Paska
Millions of people worldwide take tenofovir disoproxil fumarate (TDF) for the treatment of human immunodeficiency virus (HIV) and/or hepatitis B infection. Although generally safe and well tolerated, clinicians need to be aware that TDF can cause proximal renal tubular dysfunction and loss of bone mineral density, especially in patients with concomitant renal disease or other risk factors. We present the case of a patient with chronic HIV infection and urethral stricture who developed TDF-related proximal renal tubular dysfunction with hypophosphatemia and osteomalacia, presenting with bone pains, skeletal deformity, and disability. We review risk factors for TDF-related renal tubular toxicity and recommendations for monitoring creatinine, phosphate, alkaline phosphatase, and urinalysis.